(untitled) (Journal of Geography and Environmental Management, 2018)
In article, the condition of development of the sphere of agritourism in Kazakhstan as main way of improvement of a condition of rural regions of the republic and increase in their value as mini tourism centers with use of foreign experience of development is considered. Agritourism is a services sector in rural areas. Here for visiting guests there are organized rest, food, excursion services, the organization of sport events in free time, hobby for an active type of tourism, fishing, hunting, complex services in improvement of knowledge and skills. According to the public, for preparation of a complex tourist product in agro tourism features of resources of agriculture, natural, historical, cultural and other resources of rural areas are used. In present time, agro tourism is widely developed in Europe. Annually Italy, France, Spain accept several million agro tourists. Russia and Belarus support this type of tourism as one of sources of financial income and are at a development stage. In article are studied, works on carrying out research works on foreign experiences in the district of Martuk of the Aktyubinsk region.